The taxidermist's apprentice: stitching together the past and present of a craft practice. (July 2016) - Patchett, Merle
How do you witness the development and reproduction of a craft practice? This essay explores this provocation in relation to the craft practice of taxidermy and, in so doing, aims to stitch together non-representational and historical geographic concerns within the discipline. Mobilising and developing on an Ingoldian perspective on the process of skill, the author places herself in the position of apprentice to a practising taxidermist in recognition that the position of learner is a highly instructive context in which to enquire into how present-day practice relates to a representational culture charting the development of the craft in historical 'how-to-do' manuals. When juxtaposing contemporary ethnographies of taxidermy practice with descriptions of practice in historical 'how-to-do' manuals, the author shows how past and present practice resonates rather than replicates. Overall, this article aims to introduce and develop theoretical and methodological pathways for studying and storying (historical) geographies of craft and skilled practices.